2015
DOI: 10.1016/j.amjmed.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet, its Components, and Cardiovascular Disease

Abstract: One of the best studied diets for cardiovascular health is the Mediterranean diet. This consists of fish, monounsaturated fats from olive oil, fruits, vegetables, whole grains, legumes/nuts, and moderate alcohol consumption. The Mediterranean diet has been shown to reduce the burden, or even prevent the development, of cardiovascular disease, breast cancer, depression, colorectal cancer, diabetes, obesity, asthma, erectile dysfunction, and cognitive decline. This diet is also known to improve surrogates of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
447
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(479 citation statements)
references
References 110 publications
11
447
0
21
Order By: Relevance
“…In fact, the most replicated clinical data informing on dietary recommendations for the prevention of depression indicates the benefits of increased consumption of fruit, vegetables, legumes, whole-grain cereals, nuts and seeds, fish rich in omega-3 polyunsaturated fatty acids as well as the limitation of the intake of processed-foods, 'fast' foods and commercial bakery goods 168 . The following of traditional diets mainly composed with the above-mentioned healthy products, including the Mediterranean, Norwegian or Japanese diet, has been associated with decreased inflammation associated with cardiovascular disease and metabolic syndrome 169 . In addition, the Mediterranean diet has been associated with improvements in depressive symptoms as well 170 .…”
Section: The Influence Of Diet On Tumorigenesis and Depressionmentioning
confidence: 99%
“…In fact, the most replicated clinical data informing on dietary recommendations for the prevention of depression indicates the benefits of increased consumption of fruit, vegetables, legumes, whole-grain cereals, nuts and seeds, fish rich in omega-3 polyunsaturated fatty acids as well as the limitation of the intake of processed-foods, 'fast' foods and commercial bakery goods 168 . The following of traditional diets mainly composed with the above-mentioned healthy products, including the Mediterranean, Norwegian or Japanese diet, has been associated with decreased inflammation associated with cardiovascular disease and metabolic syndrome 169 . In addition, the Mediterranean diet has been associated with improvements in depressive symptoms as well 170 .…”
Section: The Influence Of Diet On Tumorigenesis and Depressionmentioning
confidence: 99%
“…400 BC), the concept of "food as medicine and medicine as food" has been followed and practiced among the different Western cultures. In the last few decades, several studies have shown that the Mediterranean diet can improve human health [1][2][3], particularly in relation to: a lower prevalence of cardiovascular disease [4][5][6][7][8][9], a possible effect on body weight and obesity regulation [10][11][12], a lower risk of type-2 diabetes mellitus [13][14][15], and to longevity improvement [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Она характеризу-ется обильным использованием оливкового масла, высоким уровнем потребления растительных продук-тов (фруктов, овощей, бобовых, круп, орехов и семян), частым, но умеренным приемом вина (особенно крас-ного) во время еды, умеренным потреблением рыбы, морепродуктов, молочных продуктов, птицы и яиц и низким содержанием красного мяса и сладостей [5].…”
unclassified
“…Например, есть сви-детельства благоприятного воздействия средиземно-морской диеты на резистентность к инсулину и зависящую от эндотелия вазореактивность, а также антиоксидантное и противовоспалительное действие средиземноморской диеты и ее отдельных компонен-тов, таких как фрукты и овощи, оливковое масло, цельные зерна, рыба и красное вино [17]. Кроме того, средиземноморская диета была связана с положи-тельным эффектом на многие факторы риска ССЗ, включая липопротеины, ожирение, сахарный диабет и гипертонию [5,11,18].…”
unclassified